Legal Analysis of Legal Protection Against Termination of Employment (PHK) by Companies Towards Breastfeeding Mothers Providing Exclusive Breastfeeding as Regulated by Presidential Regulation No. 2 Of 2022 Concerning Job Creation - Aulia Ramadhan; Beni Satria; Irsyam Risdawati (LPPM Universitas Ekasakti Padang, 2023)
This research aims to analyze the legal protection against Termination of Employment (PHK) by companies towards breastfeeding mothers providing exclusive breastfeeding, based on Presidential Regulation No. 2 of 2022 Concerning Job Creation. The research employs a normative legal research method, examining legal regulations, doctrines, and principles relevant to the legal protection of breastfeeding mothers providing exclusive breastfeeding. In order to support the implementation of Presidential Regulation No. 2 of 2022 concerning Job Creation, there is a need for collaboration and coordination among the government, businesses, cooperatives, MSMEs, and labor force. The government must ensure that this policy is implemented fairly, taking into account workers' rights and sustainable economic empowerment. Cooperation from all relevant parties is key to achieving the goals of this structural reform in the context of the complex global economic conditions. Although Presidential Regulation No. 2 of 2022 concerning Job Creation does not specifically regulate the rights of breastfeeding workers, women workers breastfeeding at the workplace are still protected by the Labor Law. This includes the right to leave, time and facilities for breastfeeding, as well as a prohibition on termination of employment on the grounds of breastfeeding. Despite the impact of this regulation on the labor sector, it is crucial to monitor and evaluate its implementation periodically to ensure that the goals of worker protection and economic empowerment are achieved as expected.